SYNTHESIS AND CHARACTERIZATION OF SILVER NANOPARTICLE FROM COUROUPITA GUIANENSIS LEAF EXTRACT AND ITS EFFECT ON CLINICAL PATHOGENS - JOSEPH, DEVAKUMAR; BASKARAN, SINDHUJA; NAGARAJAN, MADURI; SIVASUBRAMNIAN, SUDHA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: In this study, a rapid and simple approach was applied for the synthesis of silver nanoparticle (AgNP) from aqueous leaf extract of Couroupita guianensis. The plant extract acts as an antimicrobial agent and is also used to synthesis AgNP. Methods: Ultraviolet (UV)–visible spectrophotometer was used to characterize synthesized AgNP and to identify the compounds responsible for the reduction of silver ions, the functional groups present in plant extract were investigated by Fourier transform infrared. Agar well diffusion method was used for the antibacterial activity of synthesized AgNPs. Results: UV–visible spectrophotometer showed an absorbance peak in the range of 405 nm. The AgNPs showed antibacterial activities against Escherichia coli, Staphylococcus aureus, Streptococcus pyogenes, Bacillus sp, Klebsiella sp, and Pseudomonas sp. Conclusion: Nowadays, silver-based topical dressing has been widely used as a treatment for infections such as wounds, burns, and chronic ulcer.